2022
DOI: 10.3389/fmicb.2022.807076
|View full text |Cite
|
Sign up to set email alerts
|

Polysaccharide Regulation of Intestinal Flora: A Viable Approach to Maintaining Normal Cognitive Performance and Treating Depression

Abstract: The intestinal tract of a healthy body is home to a large variety and number of microorganisms that will affect every aspect of the host’s life. In recent years, polysaccharides have been found to be an important factor affecting intestinal flora. Polysaccharides are widely found in nature and play a key role in the life activities of living organisms. In the intestinal tract of living organisms, polysaccharides have many important functions, such as preventing the imbalance of intestinal flora and maintaining… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 98 publications
0
4
0
Order By: Relevance
“…Polysaccharides and the production of SCFAs by the gut microbiota have been reported to improve mucus secretion and increase tight-junction protein expression [ 72 , 73 ]. Metabolites produced by gut microbiota have also been shown to improve cognitive function through modulation of the brain–gut axis [ 74 ]. A polysaccharide derived from Polygonatum sibiricum has been reported to reduce hippocampal oxidative stress, activation of NF-κB, inflammatory response in lipopolysaccharide, and chronic unpredictable mild stress-induced depression in models [ 75 ].…”
Section: Resultsmentioning
confidence: 99%
“…Polysaccharides and the production of SCFAs by the gut microbiota have been reported to improve mucus secretion and increase tight-junction protein expression [ 72 , 73 ]. Metabolites produced by gut microbiota have also been shown to improve cognitive function through modulation of the brain–gut axis [ 74 ]. A polysaccharide derived from Polygonatum sibiricum has been reported to reduce hippocampal oxidative stress, activation of NF-κB, inflammatory response in lipopolysaccharide, and chronic unpredictable mild stress-induced depression in models [ 75 ].…”
Section: Resultsmentioning
confidence: 99%
“…Given the importance of gut flora, alterations in its composition have been associated with the pathogenesis of numerous acute and chronic diseases, such as diabetes, obesity, inflammatory bowel disease (IBD), Crohn's disease, autism, Alzheimer's disease, Parkinson's disease, anxiety, and depression [40][41][42][43] . For instance, studies have shown that 7-11% of patients diagnosed with IBD also have psoriasis, primarily linked to gastrointestinal www.nature.com/scientificreports/ inflammation 44 .…”
Section: Gut Microbiotamentioning
confidence: 99%
“…Some researchers have pointed out that the mechanism is achieved through the modulation of brain function, biological and immune barriers. The polysaccharide molecules in natural products can usually be used in multiple targets with significant therapeutic effects and fewer side effects ( Wang et al, 2022b ). However, there are fewer reports on the relationship between polysaccharides and depression.…”
Section: Introductionmentioning
confidence: 99%